Acquiring bilinguality : a multiple case study of Russian-speaking bilinguals in Reykjavik - Maria Shukurova 1984- (2015)
The present study investigates language and literacy acquisition in five Russian-speaking bilingual children living in Reykjavik. Explorative in its nature, the study is designed to provide information on the subjects’ language and literacy acquisition in addition to contributing to studies of multilingual children in Iceland. The research strategy adopted was a holistic multiple-case study conducted in one national context, in order to answer the following questions: What sociolinguistic and cultural factors influence the acquisition of language and literacy among Russian-speaking 7- to 9-year-old children living in Iceland? Why and how do these factors influence and interact in the children’s acquisition of L1/La and L2/Lb? Data collection techniques were oral language observations, parents’ questionnaire, language proficiency tests and decoding/encoding exercises. An Icelandic adaptation of PPVT-4 (Peabody Picture Vocabulary Test - 4) developed by Hrafnhildur Ragnarsdóttir et al. (2009; Ólafsdóttir, 2011) was used to acquire information on the participants’ Icelandic vocabulary knowledge. The Russian language proficiency test for multilingual children by Natalia Gagarina et al. (2010), oral observations and decoding/encoding exercises served to collect information regarding the participants’ oral competence and grammatical knowledge of Russian. Finally, a specifically-designed questionnaire for parents was used to collect information on the children’s home literacy environment and shed light on various socio-linguistic features. Taking into account Brian Street’s holistic concept of ideological literacy, the study attempts to examine biliteracy as both technical and socio-cultural phenomena. Predictably, the results of the PPVT-4 highlighted that the participants from a predominantly Icelandic background performed better in the test than those from chiefly Russian households. Therefore, access to the language, the number of years spent in Iceland, simultaneous or consecutive type of bilinguality, future plans ...